2015
DOI: 10.1039/c4gc01673d
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalyzed graphitization of biomass

Abstract: Nanostructured graphitic carbon with tunable mesoporosity is synthesized in one step from raw biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
143
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(159 citation statements)
references
References 26 publications
12
143
0
Order By: Relevance
“…Hitherto, various natural carbon precursors were investigated, such as sawdust 24,25 and (hydrothermally treated 26−28 ) saccharides. 29 Furthermore, only a few papers have dealt with the metal-catalyzed graphitization of (native) cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, various natural carbon precursors were investigated, such as sawdust 24,25 and (hydrothermally treated 26−28 ) saccharides. 29 Furthermore, only a few papers have dealt with the metal-catalyzed graphitization of (native) cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, polymers first decompose to amorphous carbon (AC), after which AC, as the solid carbon source, dissolves in and precipitates out of the catalyst [16][17][18][19][20][21]. The dissolution and precipitation of AC is affected by the thermal treatment temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a catalytic thermal treatment synthesis process has been developed for converting renewable biomass and biopolymers to CBNs, where renewable biomass and biopolymers such as sawdust, saccharides, lignosulfonate, and acetic acid lignin are thermally treated at 800 to 1200 • C using transition metal particles and various metal salts as catalysts [13][14][15][16]. Although the catalytic thermal treatment of biopolymers is a green and promising route for the production of CBNs, the low purity of the products and the difficulty of regulating the formation process remain problems, because these biopolymers show heterogeneity in both structure and composition [13].…”
Section: Introductionmentioning
confidence: 99%
“…18, 41 The catalytic graphitization of other biomass like so wood was conducted by Thompson et al 22 and our group 23 recently and both observed graphitized carbon and mesopore formation in the carbonized products. A few key steps for the catalytic graphitization has been proposed: (1) thermal decomposition of iron precursor Fe(NO 3 ) 3 to form iron oxide nanoparticles; (2) carbothermal reduction of iron oxide to produce Fe 3 C nanoparticles.…”
Section: (D)mentioning
confidence: 99%
“…Over the past decade, biomass derived carbon has aroused great interest in the research eld and also nd wide application in energy storage such as sodium ion battery, 18 supercapacitor 19,20 as well as environmental remediation in adsorption based water purication. 16,[21][22][23] Researchers have fabricated carbon adsorbents from various biomass resources, such as cotton, 21 bamboo, 24 vetiver roots, 25 oil palm wood, 26 rattan sawdust, 27 rice husk, 28,29 banana stalk, 30 peanut shell 31 and successfully used them as adsorbents for either heavy metal or organic pollutants removal from polluted water. Adsorbents those are capable of removing both organic and inorganic pollutants are of great interest and practically useful, while very rare work has been reported so far with both capabilities.…”
Section: Introductionmentioning
confidence: 99%